Unjust punishment in organizations. (2018) - Mooijman, Marlon; Graham, Jesse
Abstract: What causes leaders to punish subordinates unjustly? And why might leaders keep punishing subordinates unjustly, even when this increases workplace misconduct? In the current paper we address these questions by suggesting that power and status cause leaders to punish unjustly. We review evidence on the effects of power and status on punishment, review how unjust punishments foster misconduct, and highlight how this creates a self-perpetuating feedback loop—leaders are more likely to punish in an unjust manner when subordinates engage in misconduct, but subordinates' misconduct is partly caused by unjust punishments. We also discuss how leader-subordinate distrust may be at the heart of this phenomenon and how organizations may counteract unjust punishments. We draw attention to research areas that have received little attention and draw up an agenda for future research. Taken together, we integrate the literatures on power, status, punishment and trust, review evidence on when unjust punishments become perpetuating, challenge research suggesting that leaders are cautious when punishing, and guide future research on the topic of punishment in organizations.